Antibacterial activity of palm heart extracts collected from Iraqi Phoenix dactylifera L - Sameer Mohammed Yaseen; Hussein Adil Abid; Anwar Ali Kadhim; Entesar Emhamed Aboglida (Journal of Techniques)
This study aimed to assess the antibacterial activity of palm heart (Phoenix dactylifera L.) extract in vitro. Fresh material of the palm heart was dried, crushed and then extracted with distilled water, methanol and acetone. Distilled water extract was divided into crude, residues (after filtration), protein and non-protein parts. All extracts were investigated to determine their inhibitory activity against Staphylococcus aureus (S. aureus), Streptococcus pyogenes (S. pyogenes), Streptococcus mutans (S. mutans), Escherichia coli (E. coli), Klebsiella pneumoniae (K. pneumoniae), Proteus mirabilis (P. mirabilis), Enterobacter aerogenes (E. aerogenes), Morganella morganii (M. morganii), and Pseudomonas aeruginosa (P. aeruginosa) using agar well diffusion method, ceftriaxone (CTR) was used as a positive control. Phytochemical analyses were also performed to confirm the presence/absence of bioactive constituents. All extracts revealed antibacterial activity against some of the tested bacteria. When comparing the findings, aqueous (watery) extracts had the slightest antibacterial activity while the highest activity was related to acetone extraction. For Gram-positive bacteria, the highest activity of acetone extract was against S. mutans (10.7±0.13 mm) followed by S. pyogenes (10.6±0.17 mm), while Gram-negative most sensitive strain were E. aerogenes (15.3±0.20 mm) and P. mirabilis (14.4±0.48 mm) respectively. Phytochemical analyses have revealed the presence of steroids, alkaloids, pseudotannins, glycosides, carbohydrates, and aromatic amino acids. Finally, these findings indicate the activity of the heart of palm to fight germs, further studies may also be needed